Proposed IT Governance at Hospital Based on COBIT 5 Framework - Nugroho, Heru (School of Applied Science, Telkom University, 2017)
Information Technology (IT) Governance in Hospitals describe how to create an IT governance process that increases the number of IT projects that support the strategy of a hospital and are completed on-time and on- budget. Good IT governance aligns decisions about the use of IT with desired behaviors and organizational objectives. The existence of good IT governance at Hospitals is expected to provide improvement on quality,functionality, and ease of use of the service. Enablers in COBIT 5 framework can be applie in practical situations and can be used to implement effective and efficient information governance and data management of IT governance for Hospital. In this paper, we propose IT governance in Hospital base on COBIT 5 framework. In the preparation of the proposed IT governance model, the enablers that exist in COBIT 5 framework is used as a determining factor. For performing the optimization of IT services to achieve the normal vision andmission uses base on a model of IT governance for a hospital.